Impact of summarizing and translation technology in online information transfer - Seljan, Sanja; Pešorda, Barbara; Stojanac, Mara (2014)
Abstract In recent years media and online translation technology have emerged as a point of interest occurring in information access, information literacy, in education, business, etc. Aiming to enable multilingual information transfer, communication, understanding and dialogue, use of this type of technology still requires awareness about technological possibilities which can influence the reader’s perception and text understanding. Translation technology along with summarizing technology has opened new possibilities and perspectives providing quick and easy translation into another language, requiring in the same time the critical opinion in information analysis. The main purpose of this research is to present the impact of text summarization and online machine translation tools on information transfer. In the summarizing process of condensing a source document into its shorter version, the aim is to preserve the information content and the original text meaning. Summarized text can be machine-translated by use of freely available online translation technology. In the research the role of both technologies are analysed.
Projekt MZOS
Projekt MZOS
ENG